Ferning, Schimer I and Tear Break Up Time (TBUT) Accuracy Test in Post-Operative Cataract Patient with Extra Capsular Cataract Extraction (ECCE) Technique - Anang Tribowo; Alie Solahuddin; Lady Kavotiner; Theodorus; Vidya Hestika (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
A B S T R A C TObjective: To determine the accuracy of the Ferning, Schimer I and TBUT test incataract patients after cataract surgery with the ECCE technique at the EyePolyclinic at Mohammad Hoesin Hospital Palembang and the Special Eye HospitalPalembang Methods: Diagnostic test was undertaken at the Eye Polyclinic atMohammad Hoesin Hospital Palembang and the Special Eye Hospital Palembangfrom May 2019 to January 2020. There were 42 postoperative cataract patients whomet the inclusion criteria. Ferning, Schimer I and TBUT tests were performed beforesurgery and one month after surgery. Data analysis using SPSS version 22.0 (SPSS,Inc Chicago, Illinois). Results: Fourty two samples of postoperative cataract surgerywith ECCE technique obtained by female sex (57,1%) with a mean age of cataractpatients of approximately 58.09 years. The accuracy of Schimer I and TBUT is 0.952with 100% sensitivity, 50% specificity, 95% positive predictive value (PPV) and 100%negative predictive value (NPV), the accuracy of TBUT and Ferning is 0.881 with90.2% sensitivity, 0% specificity , positive predictive value (PPV) 97.4% and negativepredictive value (NPV) 0% while the accuracy of Ferning and Schimer I was 0.928with a sensitivity of 97.5%, specificity of 0%, positive predictive value (PPV) of 95.1%and negative predictive value (NPV) 0%. Conclusion: Schimer I test is more accurateto use as a predictor of dry eye in postoperative cataract patients than Ferning andTBUT